Prostate-specific antigen: Its relationship with alcohol intake and tobacco - Escandriolo Nackauzi, Jorge Dario (2012)
To determine the influence of alcohol and tobacco consumption on serum prostate-specific antigen (PSA) levels. 59 men participated in this study: 20 with prostate tumors (PT) and 39 without tumor diagnosis (prostate controls, PC) (mean 66 and 58 years, respectively). PSA was analyzed in serum samples and its values were compared through the Kruskal-Wallis nonparametric test. Alcohol and tobacco consumption was also considered. PSA mean value was higher than 4 ng/ml in PT, whereas in PC it was lower than that value. Statistically significant differences were found when comparing PSA between PT and PC (P<0.05). PSA was higher in alcohol and tobacco consumers than in non-consumers in PT group (P<0.05). For PC, PSA mean values were higher in nonsmokers than in smokers. Statistically significant differences were observed for serum PSA when compared between PT and PC groups considering alcohol and tobacco consumption (P<0.05). Serum PSA values appear to be influenced by alcohol and tobacco consumption.